FENOMENA USAHA SAMPINGAN SEBAGAI BENTUK KEWIRAUSAHAAN MAHASISWA DI ERA DIGITAL - Natalia Sari Pujiastuti; Abdul Rahman Bin Rahim; Chrisnanda Dicky Kurniawan; Rafi Danendra Rizaldi; Rifan Adi Kurniawan; Sultan Rafi Arya Putra (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
The development of digital technology has created various entrepreneurial opportunities for university students through the use of social media, marketplaces, and other digital platforms. This phenomenon has encouraged the emergence of side business as a form of entrepreneurship increasingly pursued by students to generate additional income while developing skills relevant to the needs of the digital era. This study aims to analyze the phenomenon of side business as a form of student entrepreneurship in the digital era and to identify the benefits and challenges encountered in their implementation. The research employs a literature review method by examining various scientific articles and relevant bibliographic sources. The findings indicate that side business provide benefits such as increased financial independence, development of communication skills, enhanced digital literacy, and practical experience in managing a business. However, students also face various challenges, including time constraints, lack of managerial experience, and intense competition in the digital business landscape. Therefore, support from higher education institutions through entrepreneurship education and digital literacy programs is needed to improve students' readiness to develop sustainable businesses.